Intergovernmental Fiscal Relations - Anderson, William, 1888-1975 (Intergovernmental relations in the United States ;, 1956)
Intergovernmental Fiscal Relations was first published in 1956. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. This volume is number 8 in a series of monographs edited by William Anderson and Edward W. Weidner on intergovernmental relations in the United States as observed in the state of Minnesota. Topics discussed include: the financial problems of a federal system; Minnesota's place and rank in the union; the financial relationship between Minnesota and the nation from 1783 to 1953; the respective financial powers of Minnesota and the nation; national and state taxes in Minnesota; federal grants-in-aid as a revenue source; the national-state fiscal balance; state-local revenue relations; and state payments to local governments.